COMPREHENSIVE PUBLIC SMOKING PROGRAM BUDGET (Tufts Archival Research Center, 2007)
Marginalia; Confidential; Budget outlining the expenditures of a comprehensive public smoking program. Assigns funds to scientific affairs, corporate/smoker assistance, indoor air quality, social costs, conflict resolution, smokers' rights groups and smokers as customers. Specifies fees for printing, advertising, professional services and support to tobacco and other organizations for each category.